2008
DOI: 10.1002/app.29243
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and properties of polymeric flocculant with the function of trapping heavy metal ions

Abstract: A novel crosslinked starch-graft-polyacrylamide-co-sodium xanthate (CSAX) was synthesized by grafting copolymerization reactions of crosslinked corn starch, acrylamide (AM), and sodium xanthate, using epichlorohydrin (EPI) as crosslinking reagent and ceric ammonium nitrate as initiator in aqueous solution. The effects of some factors, such as crosslinker, initiator, AM, NaOH and so forth, on the flocculation were investigated in terms of efficiency of grafting (% GE), grafting percentage (% GP), and viscosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Preparation of Crosslinked Starch (CSt) [6,7] Corn starch (50g) and 1% (w/v) sodium chloride solution (75mL) were put in a 250mL three-necked flask equipped with a stirrer and a thermometer. The slurry was heated to 30℃ and kept at the constant temperature in water bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of Crosslinked Starch (CSt) [6,7] Corn starch (50g) and 1% (w/v) sodium chloride solution (75mL) were put in a 250mL three-necked flask equipped with a stirrer and a thermometer. The slurry was heated to 30℃ and kept at the constant temperature in water bath.…”
Section: Methodsmentioning
confidence: 99%
“…In addtion to the CSAX has the length of PAM pendant chains that remove turbidity by bridging flocculation. So it is possible that the CSAX use as flocculant to reduce the subsequent units in wastewater treatment [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…91 The flocculation efficiency of polymer 62 was tested based on turbidity reduction as well as removal of Cu 2+ ions in kaolin suspension. 91,92 SX-grafted crosslinked starch (CSX) and AM-grafted crosslinked starch (CSA) were also synthesized separately in this study for flocculation comparison purposes. CSA was observed to have significantly lower Cu 2+ removal rate compared to 62 and CSX; whereas CSX showed only slightly lower Cu 2+ removal rate with respect to 62.…”
Section: Anionically-modified Polysaccharidesmentioning
confidence: 99%
“…The xanthate functional group on the flocculant underwent complexation with Cu 2+ ions to form precipitates, which were observed to be entrained by large flocs as they settled down and vice versa for fine suspended solid particles. 91,92 In addition, Cu 2+ ions also neutralized the negative charges on the suspended solids, which decreased the repulsion between the particles and the polymeric chains, hence enhanced the flocculation efficiency. 91 Mishra et al reported another modified polysaccharide 63, this time, focused on polyacrylic acid grafted onto carboxymethyl cellulose by MWI synthesis.…”
Section: Anionically-modified Polysaccharidesmentioning
confidence: 99%
“…[1][2][3][4][5][6] Also, because the amino groups can serve as chelation sites, chitosan and its derivatives are capable of adsorbing a number of metal cations and can be used as adsorbent material for the removal of metal cations from wastewater or effluents. [7][8][9][10] The modification of the polymer surface through the introduction of new complexation groups may result in the formation of efficient chelates, which thus increases its adsorption capacity and selectivity toward metal ions in solution. [11][12][13] Generally, various studies have been conducted to make derivatives of chitosan by chemical modification techniques, such as grafting, sulfonation, quaternization, hydroxylation, and carboxymethylation.…”
Section: Introductionmentioning
confidence: 99%